Nature of Computation and Communication Second International Conference, ICTCC 2016, Rach Gia, Vietnam, March 17-18, 2016, Revised Selected Papers - Vinh, Phan Cong; Barolli, Leonard (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering,, 2016)
This book constitutes the post-conference proceedings of the Second International Conference on Nature of Computation and Communication, ICTCC 2016, held in March 2016 in Rach Gia, Vietnam. The 36 revised full papers presented were carefully reviewed and selected from over 100 submissions. The papers cover formal methods for self-adaptive systems and discuss natural approaches and techniques for computation and communication.